PENGUATAN SISTEM PRESIDENSIIL MELALUI SISTEM PEMILU - Siti Ngaisah, Siti Ngaisah (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2019)
Another implication of the fundamental changes to Article 1 Paragraph (2) of the 1945 Constitution to the 1945 Constitution of the Republic of Indonesia is that the position of the president has the same legalization and legitimacy as the legislative because both are produced through General Elections. On the basis of these changes Article 1 Paragraph (2) of the 1945 Constitution and the election system of the President and Vice President directly negated the confusion of the government system adopted in Indonesia so that the government system adopted by the Indonesian state after the amendment to the 1945 Constitution was a pure presidential system. Simultaneous general elections are recommended by the Constitutional Court through verdict Number 14/PUU-XI/2013 The Constitutional Court's decision was then declared in Article 167 of the Election Law. One of the bases of simultaneous elections is the stability and effectiveness of government after the election. Stability will be created where the president has great support in parliament. Simultaneous elections can harmonize the president's electability with the electability of members of the DPR because in simultaneous elections it creates a coattail effect. Thus the presidential system that is implemented in a country requires simplification of political parties because the presidential system does not fit into the multi-party system and the parliamentary threshold system is one solution to the problem.